Analysis of Financial Performance Before and During the Covid-19 Pandemic in Indonesia - Diningrat, Athaya Sukma; Herlina Pusparini; Robith Hudaya (ARRUS Journal of Social Sciences and Humanities, 2023)
This study aims to analyze whether or not there is a difference between financial performance before and during the covid-19 pandemic in Indonesian companies from 2019 to 2020. The financial ratios used are return on asset, current and debt to equity ratios. The population in this study are companies included in the go-public companies in the tourism, restaurant and hotel sub-sectors from 2019 to 2020. Sampling was carried out by the purposive sampling method. So we obtained 37 companies as a sample. The data analysis method used is the Wilcoxon signed rank test, previously carried out descriptive statistical tests and normality tests first. The data analysis showed significant differences between return on asset, current ratio, and debt to equity ratio before and during the covid-19 pandemic.